Risk factors of stroke survivors' quality of life - Candrawati, Oktania; Wirasto, Ronny Tri (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2017)
Background : Stroke can lead into long-term disabilities which may affect stroke survivors' quality of life (QOL). The importance of stroke survivors' QOL is still getting little attention. Objective : To know stroke survivors' QOL and the risk factors associate with, i.e.:sociodemographic, activity daily living, cognitive, and depression. Methodology : This cross-sectional study was conducted in April-October 2014 at neurology clinic Dr.Sardjito Hospital, Yogyakarta. Subjects' criteria were minimal four weeks after the first stroke incident and came with their primary caregiver. Subjects were interviewed about their sociodemographic condition and were given WHOQOL-BREF, Mini Mental State Examination (MMSE), and Beck Depression Inventory (BDI) questionnaires. Meanwhile, their caregiver was interviewed with Barthel Index (BI) questionnaire. Bivariate chi-square and logistic regression analysis was done. Results : There were 64 subjects analyzed. QOL domain affected the most is physical, while the least is environment. Bivariate analysis found not working after stroke and higher BDI score associate with lower WHOQOL-BREF physical (r=9.286, p<0.01 and r=5.361, p<0.05) and psychological (r=3.935, p<0.05 and r=14.527, p<0.001) domain. No risk factor associates with WHOQOL-BREF social relationship domain. Higher BDI score associates with lower WHOQOL-BREF environment domain (r=5.861, p<0.05). Regression analysis shows older age (p<0,05) and not working after stroke (p<0,01) are risk factors for lower WHOQOL-BREF physical domain, while higher BDI score is risk factor for lower WHOQOL-BREF psychological (p<0,01) and environment (p<0,05) domain. Conclusions : Older age and not working after stroke incident are risk factors for physical domain of QOL. Depression is risk factor for psychological and environment domain of QOL.